Purchase decisions for standard needs at Puri Taman Sukawati company - Ghannesvara, Anak Agung Gde Garga; Rahanatha, Gede Bayu (International research journal of management, IT and social sciences, 2023)
This study aims to find out and analyze the effect of Customer solutions, Customer cost and Convenience on the psychological consumers of Toko Puri Taman Sukawati, and to find out and analyze the psychological influence of consumers on the purchasing decisions of consumers of Toko Sukawati Park Castle. The population used is customers who have purchased Puritaman basic necessities products domiciled in Sukawati district, the number of which cannot be mentioned or calculated with certainty (infinite). The sampling technique used in this study is purposive sampling technique. The number of sample members or sample size (sample size) set in this study was 95 respondents. Data collection was carried out using questionnaire tools. The analysis technique used is multiple regression analysis.